Thunder game [large type] - Feehan, Christine (Feehan, Christine. GhostWalker novel., 2025)
"Diego Campos has come home to die. The GhostWalker is tired of walking a dark path shaped by countless losses. There has never been a moment of good in his life that wasn't followed by something bad. But as he makes his way to his family's homestead in the Appalachian Mountains, his plans are interrupted by a violent ambush that sets his life on a new course. In between fighting off a small army of assailants, Diego is struck by a beautiful, brutal warrior woman unlike anyone he's encountered before. Compelled to rescue her, Diego uses his psychic gifts to make Leila's broken body whole again and save her from certain death. With each new breath she regains her strength, showcasing her humor, intelligence and courage as she reveals the truths of her past and inspires feelings Diego never thought his heart could experience. After a lifetime alone, in the middle of firefight, Diego has finally found a light to guide him through the darkness--and one brief touch is enough to set them both aflame." -- Amazon.